Inteligência artificial para testes de software - Boni, Nathaelly (Universidade Federal de São Carlos, 2024)
The software development process is essential for applications used on a daily basis. Part of this process involves the stage of software testing, responsible for revealing the presence of defects and improving the application's efficiency. This step can be very costly and laborious, therefore there are several ways to optimize time. Artificial Intelligence (AI) can be used in this stage, bringing several benefits and improvements to both the budget and the optimization of the software itself. This work addresses the intersection between these two areas, reviewing some works that experiment with different ways of applying AI to software testing. The results indicate that the area is progressing and is very promising, but there is still many details to be explored. The results demonstrate that artificial intelligence can increasingly help to develop good quality software.
Artificial intelligence for software testing
Keywords: Inteligência artificial; Teste de Software; Engenharia de software; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO